Escrita e práticas interlocutivas na sala de aula: aspectos discursivos na produção de artigo de opinião e de relato de memória - Souza, Renata Herwig de Moraes (2018)
According to Geraldi and Citelli (2011), the practices of text analysis in classroom have improved the work with text into a kind of cleaning operation, 'hygiene', in which the main objective is to take out mistakes in the textual surface. Contrary to this view, we defend the idea of writing texts in schools because it is an essential activity to promote the students' contact with the world of writing. Therefore, it is relevant to develop in the researched school teaching practices focused on work with discursive genres. For it, we promote the development of language acts, whose vision refers to writing as a social and interactional activity. We consider as main objective, the development of a teaching proposal of textual production, to identify the linguistic and discursive resources that sustains the writing practice. To produce it, we read several theorists, especially Bakhtin's ([1959] 2011) about the ideological nature of linguistic signs, discourse genres and notions of text, and Antunes's (2010) analysis categories, as a focus on global aspects, vocabulary adequacy and its construction. The study has used researches of Antunes (2003, 2009) and Geraldi (2006), around the work with text in classroom and reflections about language conception in teaching practice. We have used Koch (2012) regarding the construction of the argumentation. In addition, about the teaching practices of gender and text, we used the Parâmetros Curriculares Nacionais. In relation to the ideological and social character of language we used the studies of Bakhtin / Volochinov ([1929] 2006). The methodology used, we chose the qualitative research-action, and the locus was a full time high school. We verified the amplification of the level of informativeness can corroborates to increase the students' discursive competence. The research observed the aspects of vocabulary adequacy are linguistic factors linked in the level of theme progression and the reference marks, showing that, pedagogically, the interactive practices are important aspects to extend the linguistic and discursive students’ competence and the teacher mediation places students in written production.